2003
DOI: 10.1111/j.1365-2435.2003.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Gall initiation enhances the availability of food resources for herbivorous insects

Abstract: Summary1. Insect herbivory may have not only negative but also positive plant-mediated effects on other insect herbivores. We investigated plant-mediated effects of the stem gall midge Rabdophaga rigidae on other insect herbivores through regrowth response of the willow Salix eriocarpa. 2. Gall initiation on current-year shoots stimulated the development of lateral shoots, followed by a secondary leaf flush. Lateral shoots and upper leaves on galled shoots were less tough and had a higher water and nitrogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 36 publications
0
84
1
Order By: Relevance
“…obs.). On Salix, insect stem galls increased the growth of lateral shoots, which were then less tough and had higher nitrogen and water contents (Nakamura et al, 2003). In addition to increased food resources, evacuated galls provide structural heterogeneity on Metrosideros, and Collembola and Psocoptera were observed foraging or residing within excavated gall tissues on leaves or stems.…”
Section: Community Responses To Foliar Pubescencementioning
confidence: 99%
See 1 more Smart Citation
“…obs.). On Salix, insect stem galls increased the growth of lateral shoots, which were then less tough and had higher nitrogen and water contents (Nakamura et al, 2003). In addition to increased food resources, evacuated galls provide structural heterogeneity on Metrosideros, and Collembola and Psocoptera were observed foraging or residing within excavated gall tissues on leaves or stems.…”
Section: Community Responses To Foliar Pubescencementioning
confidence: 99%
“…The supply of limited nutrient resources is of fundamental importance to plant productivity and to the arthropod populations and communities on plants (White, 1984;Waring & Cobb, 1992;Kyto¨et al, 1996). Ambient plant nitrogen levels are low in comparison to consumer requirements (Mattson, 1980;White, 1984;Hartley & Crawley, 1997), and a wide variety of herbivore taxa feed preferentially on nitrogen-enriched tissues (Ball et al, 2000;Nakamura et al, 2003;Albrectsen et al, 2004). The abundance, biomass, and diversity of herbivores or detritivores and their predators often increase in fertilisation experiments in natural systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A herbivore-removal experiment in the field and a herbivore-inoculation experiment in the greenhouse showed that herbivore community composition determined the degree of herbivore-induced regrowth of the local willow populations in the field. Herbivore-induced regrowth involved phenological changes in new leaf production, where the period of new leaf production expanded dramatically (Nakamura et al 2003;Utsumi et al 2009aUtsumi et al , 2013. Where new leaves are seasonally abundant due to strong willow regrowth, populations of the specialist leaf beetle (P. versicolora) develop exclusive preference for new leaves.…”
Section: Community Context Evolutionmentioning
confidence: 99%
“…In terrestrial systems, herbivory by insects often induces trait changes in plant tissues, which indirectly affect the growth or abundance of other consumers of the same individual plants. These indirect effects can be negative, as a result of induced resistance to herbivory (e.g., Faeth 1986;Karban and Myers 1989), but can also be positive as a result of compensatory regrowth of plant tissue (e.g., Nakamura et al 2003) or of induced resistance that is effective against a certain consumer species yet actually benefits other consumers (Martinsen et al 1998). Although there are apparently many differences, we looked for functional similarities between TMIIs in aquatic microbial systems and those in terrestrial plantinsect systems.…”
Section: Comparison With Plant-insect Systemsmentioning
confidence: 99%
“…Herbivory by this arthropod can induce trait changes of leaves within the same individual plant that has not actually been subjected to herbivory, known as induced systemic resistance (e.g., Agrawal et al 1999; see also Orians 2005 for review). Insects consuming the stem tissue can also induce a change in the availability of different types of resource, e.g., leaves, and thus affect other types of consumers (Nakamura et al 2003). In a broader sense, each leaf or each module (e.g., shoot) within an individual plant can be viewed as corresponding to an individual or clonal subgroup within the bacterial assemblage and different types of resources within a given individual plant (e.g., leaves, stems, and roots) as corresponding to distinct clonal subgroups in bacterial assemblages.…”
Section: Comparison With Plant-insect Systemsmentioning
confidence: 99%